Characterization of NH\(_3\) Sensing Properties of P3HT+rGO+CNT Composite Films Made by Spin-coating - Long, Lam Minh; Dinh, Nguyen Nang; Trung, Tran Quang (Communications in Physics, 2018)
Thin films of poly(3-hexylthiophene) (P3HT) incorporated with reduced graphene oxide (rGO) and multi-walled carbon nanotubes (CNTs) were prepared by spin-coating technique. Atomic force microscope (AFM) surface morphology, UV-Vis spectra and NH3 gas sensing of the films were studied. Results showed that the P3HT embedded with a content of 20 wt.% of rGO and 10 % of CNTs (abbreviated to P3GC) resulted in the formation of nanostructured composites, exhibiting 1.50 nm-roughness surface and a semiconducting material with a bandgap of 1.92eV. These structure and composition of the P3GC film are appropriate for making film sensors whose resistance changes as a function of gas concentration. Monitoring ammonia gas by the sensors showed that the responding time of the sensing reached a value as fast as 30 s, the response at ammonia gas content of 10 ppm attained a value as large as 0.8% and the relative sensitivity was of 0.05 %/ppm.